2018
DOI: 10.21037/jtd.2018.08.18
|View full text |Cite
|
Sign up to set email alerts
|

Prehabilitation in thoracic surgery

Abstract: Surgical resection remains the best treatment option for patients with early stage of non-small cell lung cancer (NSCLC). However, it may be responsible of postoperative complication and mortality, especially in patients with impaired pulmonary function. Enhanced recovery after surgery (ERAS) programs have been focused mainly in minimal invasive surgery approach during lung resection and respiratory rehabilitation after surgery. Preoperative exercise-based intervention (prehabilitation) has demonstrated reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 34 publications
0
43
0
1
Order By: Relevance
“…Available data also shows that frailty rather than age is a major risk factor of perioperative complications (15). This evidence suggests including patient tailored physical activity in the time between diagnosis and the surgical procedure (16)(17)(18). Careful communication with the patients is of utter importance.…”
Section: Preoperative Periodmentioning
confidence: 99%
“…Available data also shows that frailty rather than age is a major risk factor of perioperative complications (15). This evidence suggests including patient tailored physical activity in the time between diagnosis and the surgical procedure (16)(17)(18). Careful communication with the patients is of utter importance.…”
Section: Preoperative Periodmentioning
confidence: 99%
“…A potential curative option for early-stage nonsmall cell lung cancer (NSCLC) is primary lung resection (1). However, physical deconditioning is a major risk factor for patients undergoing surgery, and low peak oxygen uptake (VO 2peak ) is a predictor of perioperative mortality and cardiopulmonary morbidity (2,3).…”
mentioning
confidence: 99%
“…16,17 The FACT-L version 4.0 used in this study is a Chinese version equivalent to 2000 Chinese finished by Wan Chonghua. It includes a common module consisting of a total of 34 items (physical status (8), social/ family status (8), relationship with doctors (3), emotional status (7), and functional status (8)) (i.e. The general scale of cancer treatment function evaluation (FACT-G) and the specific module used by NSCLC patients only (that is, the 10-item NSCLC additional focus part) are composed of two parts.…”
Section: Functional Assessment Of Cancer Treatment-lung Fact-l 40mentioning
confidence: 99%
“…5,6 Several studies in recent years have confirmed that lung rehabilitation training such as respiratory function exercise and muscle exercise have a positive effect on the rehabilitation of lung function after NSCLC. 7,8 However, conventional lung rehabilitation training is monotonous and boring, and the patient's compliance is poor, making it difficult to persist after discharge. In addition, patients with malignant tumors often have a series of problems in negative emotions such as anxiety, depression, fear, social function, and emotional status, which are difficult to solve by relying solely on lung rehabilitation.…”
Section: Introductionmentioning
confidence: 99%